Improved Culture from Lymph Nodes of Patients with Cat Scratch Disease and Genotypic Characterization of Bartonella henselae Isolates in Australia - Fournier, Pierre-Edouard (American Society for Microbiology, 2002)
Over a 4-year period we detected Bartonella henselae isolates in 104 of 297 specimens (35.1%) from Australian patients clinically suspected of having cat scratch disease by amplification of a fragment of the htrA gene. We isolated 17 B. henselae strains (20.5%) from the 83 PCR-positive human specimens available for culture. Our culture method was based on prolonged incubation in a moist atmosphere of blood agar to which hemin was added. We obtained more B. henselae isolates than the number of all other isolates from lymph nodes reported in the literature. In order to identify and study the genetic variation of Australian B. henselae isolates, we determined the sequence of a fragment of the pap31 gene from our 17 human isolates and also from 8 Australian cat isolates. Thirteen of the human B. henselae isolates belonged to the Houston genotype, variant Houston-1 (76.5%), and four belonged to the Marseille genotype, variant CAL-1 (23.5%). In contrast, seven cat isolates were classified as B. henselae Marseille, variant CAL-1 (87.5%), and one was classified as B. henselae Houston, variant Houston-1 (12.5%). Our study describes an efficient culture method for the diagnosis of cat scratch disease and contributes to the description of the genotypic distribution of B. henselae in Australia.